A new Catalogue of HI supershells in gthe outer part of the Milky Way - Suad, Laura Andrea (2014)
A New catalogue of H I supershell candidates (GSc) was developed in the outer part  of the Galaxy. The search was carried out using a combination of two techniques: one based on a visual inspection plus an automatic algorithm. A statistical study of the main properties of the detected structure was also carried out.